Status in world politics - Paul, T. V.; Larson, Deborah Welch, 1951-; Wohlforth, William Curti, 1959- (Cambridge : Cambridge University Press, 2014)
Rising powers such as Brazil, China, India, Russia, and Turkey are increasingly claiming heightened profiles in international politics. Although differing in other respects, rising states have a strong desire for recognition and respect. This pioneering volume on status features contributions that develop propositions on status concerns and illustrate them with case studies and aggregate data analysis. Four cases are examined in depth: the United States (how it accommodates rising powers through hierarchy), Russia (the influence of status concerns on its foreign policy), China (how Beijing signals its status aspirations), and India (which has long sought major power status). The authors analyze status from a variety of theoretical perspectives and tackle questions such as: How do states signal their status claims? How are such signals perceived by the leading states? Will these status concerns lead to conflict, or is peaceful adjustment possible?
Machine generated contents note: Part I. Introduction: 1. Status and world order Deborah Welch Larson, T. V. Paul and William C. Wohlforth; Part II. Admission into the Great Power Club: 2. Managing rising powers: the role of status concerns Deborah Welch Larson and Alexei Shevchenko; 3. Status considerations in international politics and the rise of regional powers Thomas J. Volgy, Renato Corbetta, J. Patrick Rhamey, Jr, Ryan G. Baird and Keith A. Grant; 4. Status is cultural: Durkheimian Poles and Weberian Russians seek great-power status Iver B. Neumann; Part III. Status Signaling: 5. Status dilemmas and inter-state conflict William C. Wohlforth; 6. Status signaling, multiple audiences, and China's blue-water naval ambition Xiaoyu Pu and Randall L. Schweller; Part IV. International Institutions and Status: 7. Status accommodation through institutional means: India's rise and the global order T. V. Paul and Mahesh Shankar; 8. Setting status in stone: the negotiation of international institutional privileges Vincent Pouliot; Part V. Status, Authority, and Structure: 9. Status conflict, hierarchies, and interpretation dilemmas William R. Thompson; 10. Status, authority, and the end of the American century David A. Lake; Part VI. Conclusions: 11. Why status matters in world politics Anne L. Clunan.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: World politics; International relations